Peer Attachment dengan Psychological Well-Being - Ivonisevic, Azlia; Dewi, Mahargyantari P; Pranandari, Kenes (IDEA: Jurnal Psikologi, 2025)
One of the key factors that contribute to students' success in completing their higher education is positive psychological functioning or good psychological well-being. A student's adaptation during the transition to college is influenced by several factors, one of which is socio-emotional aspects (self-confidence and relationships with peers). The purpose of this study is to empirically examine the relationship between peer attachment and psychological well-being in migrant students. This research employs a quantitative method, and hypothesis testing is conducted using Pearson’s product-moment correlation analysis. The subjects in this study are migrant students. Data collection was carried out using questionnaires to measure the Psychological Well-Being Scale (PWBS) and the Inventory of Parent and Peer Attachment (IPPA). The results indicate a highly significant positive relationship between peer attachment and psychological well-being in migrant students, with a correlation coefficient of r = 0.57 and a significance value of 0.00 (p < .01).